2016
DOI: 10.4103/2229-516x.174007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carotid arteries in stroke patients using color Doppler sonography: A prospective study conducted in a tertiary care hospital in South India

Abstract: Aims and Objectives:Cerebral ischemic stroke is life-threatening and debilitating neurological disease, it is the third leading cause of death in the world. Studies have shown that there is a close relationship between carotid artery stenosis and ischemic cerebral vascular disease. This study is done to assess the carotid arteries with the help of color Doppler sonography and to correlate cerebrovascular accidents.Materials and Methods:The prospective study was carried out on 50 patients using purposive sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 20 publications
(19 reference statements)
7
22
0
3
Order By: Relevance
“…8 A study by Fernandez et al, reported the most common age to be affected was 60-69 years. 11 Among the patients with atherosclerotic plaque, 63.4% had diabetes and 68.3% had hypertension. Around 35% of them were either smokers, or alcoholics or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 A study by Fernandez et al, reported the most common age to be affected was 60-69 years. 11 Among the patients with atherosclerotic plaque, 63.4% had diabetes and 68.3% had hypertension. Around 35% of them were either smokers, or alcoholics or both.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was also seemed to have a positive correlation in his study. 11 A study by Mannami et al, had attributed 22% of stroke patients to smoking. 12 A comparatively low association of hypertension with stroke was observed in a study by Lawes et al 13 In a study by Lindsberg The mean intima media thickness was 1.38mm among the patients with carotid plaque, with maximum being 1.8 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was the most common risk factor which is also similar to the finding of the present study. 10 Haq S et al, used CT scan to diagnose ischemic stroke in 50 patients. 11 They found that ICA/CCA PSV ratio was able to predict stenosis in more than 60% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of carotid stenosis associated with ischemic stroke has been very different in various studies. In the study by Chang et al in 2002, the prevalence of carotid stenosis was 24.3% (25), in Tan et al study in Taiwan in 2005, it was 6% (26), and in Fernandes et al study in 2016 in India was 24% (27). Overall, the incidence of carotid artery stenosis in patients with ischemic stroke appears to be visible in 6% to 24% of the patients and therefore, this finding in these patients will not predominate in the vast majority of the patients.…”
Section: Concerning the Risk Factors Associated With Ischemicmentioning
confidence: 94%